BUSINESS FEASIBILITY IN VIEW FROM THE CULTURAL ASPECT OF TOURISM AT BOROBUDUR TEMPLE - Moh Rizal; Muhammad Lutfi (IJED: International Journal of Economy Development Research, 2022)
Abstract :A business feasibility study is one of the activities based on research or studies. This study was conducted in an effort to find information whether the business to be carried out, is being carried out, or has already been carried out is feasible or not. Information on the feasibility of this business is very important to know in an effort to increase the efficiency of resource allocation, both natural resources, labor, capital, human resources, and also technology. Indonesia is rich in culture and abundant natural resources, such as spices, batik, traditional clothes, culinary, traditional houses, and tourism which is still very thick with ancient culture. one of them is the Borobudur temple which is located in the village of Borobudur, Magelang Regency, Central Java. Borobudur temple is also included in the list of the seven wonders of the world and the largest temple in the world which was built in the 9th century. The purpose of this research is to identify the business feasibility of Borobudur Temple which has been approved by UNESCO as the largest temple and the grandest stupa complex in the world. Changes in the social and cultural structures of the people in this tourist area are efforts to collectively adapt people's lives to environmental challenges that have dynamic characteristics. The existence of Borobudur Temple is a legacy of artifacts from the ancestral heritage of the Indonesian nation. This illustrates that the growth of civilization in the 8th century AD existed, and became the center of livelihood and community life for generations in the Borobudur area, covering almost all aspects of life, namely; geography, demography, natural resources,